Creating a Successful Christian Marriage - McDonald, Cleveland (Grand Rapids, Mich. Baker Books, 1994)
After twenty years in classroom use, Creating a Successful Christian Marriage has been extensively revised for a new generation. The goals of the fourth edition are to equip young people to make an intelligent choice of a mate and to help them anticipat
Keywords: Marriage -- Religious aspects -- Christianity